Explanation:
equation for a gradient is
m=(y¹-y²)/(x¹-x²)
again the ¹&² are not powers
so (x¹,y¹) and (x²,y²) would be
(-1,6) and (4,-4) respectively
so the gradient would be
(6+4)/(-1-4)
=-2
so the ans is
2=(y¹-y²)/(x¹-x²)
y¹-y²=2(x¹-x²)
y-6=2(x+4)
Note that I put (x, y) into (x¹,y¹)
and (-1,6) into (x²,y²)
(x²,y²) can also be (4,-4), which would lead to the same answer, as theyre the dots on the SAME line
For question 8, try to follow my steps, and figure out the gradient of the graph first, so u can understand what u should do when u see these kinds of questions